Hyperbaric oxygen therapy for delayed onset muscle soreness and closed soft tissue injury - Bennett, M.; Best, T. M.; Babul, S.; Taunton, J.; Lepawsky, M (Cochrane Database of Systematic Reviews, 2005)
Background Soft tissue injuries (including muscle damage after unaccustomed exercise) are common and are often associated with athletic activity. Hyperbaric oxygen therapy (HBOT) is the therapeutic administration of 100% oxygen at environmental pressures greater than one atmosphere.